Pathophysiological associations between maternal immune activation and neurodevelopmental disorders in offspring: a comprehensive review - Tang, Qing; Wang, Xiaofang; Yang, Fanqian; Liang, Lvyuan; Li, Yuxin; Liu, Wenbo; Zhou, Rongyi; Ma, Bingxiang (Frontiers in Endocrinology, 2025)
BackgroundMaternal immune activation (MIA), triggered by infectious or non-infectious inflammatory stimuli, is a critical risk factor for offspring neurodevelopmental disorders (NDDs) and has become a major focus in neurodevelopmental pathology research.ObjectiveThis study systematically examined the cellular and molecular mechanisms by which MIA disrupts fetal neurodevelopment, aiming to clarify its impact on NDDs susceptibility and to provide a basis for basic research and clinical intervention.MethodsA literature search was conducted in PubMed, Web of Science, and Scopus up to June 30, 2025. Both animal and human studies were included, while irrelevant or non-mechanistic reports were excluded. Reference lists of key articles were also screened manually to supplement the database search.ResultsMIA induces systemic elevation of inflammatory cytokines that cross the placenta, activate fetal immune responses, and impair brain development. It suppresses neural stem/progenitor cell proliferation and accelerates premature differentiation, disrupts neuronal migration, alters deep-layer neuron density, and impairs GABAergic interneuron migration. These changes cause neurogenesis and cortical layering abnormalities, increasing the risk of NDDs in offspring, such as autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD), and schizophrenia (SCZ).ConclusionInflammatory cytokines mediate MIA-induced disruptions in neural stem cell proliferation, differentiation, and migration, constituting the main mechanism of maternal impact on fetal neurodevelopment. This insight provides a basis for early diagnosis and precise prenatal intervention to reduce NDDs incidence and improve prognosis.